Global solvability of a class of reaction–diffusion systems with cross-diffusion. (February 2022) - Wang, Zhi-An; Wu, Leyun
Abstract: This paper is concerned with a class of reaction–diffusion systems with cross-diffusion which have various applications such as autocatalytic chemical reaction, predator–prey interactions, combustion and so on. By imposing some suitable structure assumptions, we establish the global existence and asymptotic behavior of solutions of the system in a two-dimensional bounded domain with Neumann boundary conditions.